Effect of threonine supplementation level on performance of male ross 308 broiler chickens fed a diet containing cellulase - Sebati, Mosima Petronella (My University, 2024)
An experiment was conducted to evaluate threonine supplementation levels for optimal performance and carcass quality of male Ross 308 broiler chickens aged 22 to 42 days and fed diets mixed with a cellulase enzyme. The diets were isocaloric and isonitrogenous but with different dietary threonine levels. A complete randomized design was used. The treatments were CT4 (4 g of threonine/kg DM), CT5 (5 g of threonine/kg DM), CT6 (6 g of threonine/kg DM) and CT7 (7 g of threonine/kg DM) g of threonine/kg DM. A quadratic type of equation was used to determine dietary threonine levels for optimal performance of the chickens. Dietary threonine levels of 4, 5, 6 or 7 g/kg DM used in the present study had no effect (P>0.05) on feed intake, dry matter (DM) digestibility, live weight, live weight gain, feed conversion ratio (FCR), metabolizable energy (ME) intake and nitrogen retention of male Ross 308 broiler chickens. Dietary threonine levels had no (P>0.05) effect on gut organ digesta pH values, gut organ lengths and gut organ weights of Ross 308 broiler chickens aged 42 days. Dietary threonine level had no effect (P>0.05) on wing weights of the chickens aged 42 days. However, threonine level in the diet affected (P<0.05) carcass, thigh, drumstick, breast and abdominal fat weights of the chickens. Carcass, thigh, drumstick and abdominal fat weights were optimized at dietary threonine levels of 1.58, 3.12, 3.52 and 5.13 g of threonine /kg DM, respectively. Dietary threonine level had no effect (P>0.05) on meat lightness and yellowness of the chickens. However, threonine level in the diet affected (P<0.05) red colour of the meat. A dietary threonine level of 5.80 g per kg DM was calculated to result in optimal redness of the meat. Threonine levels did not affect (P>0.05) thigh, drumstick, and breast pH values of the chickens. However, dietary threonine level affected (P<0.05) wing and abdominal fat pad pH values; and a dietary threonine level of 6.1 g/kg DM was calculated to result in optimal wing and abdominal fat pad pH values of male Ross 308 broiler chickens. Dietary threonine level did not affect (P>0.05) meat flavour and juiciness values. However, dietary threonine level affected (P<0.05) meat tenderness, shear force and water holding capacity values of the chickens. A dietary threonine level of 4.78 g per kg DM was calculated to result in optimal meat tenderness of the chickens. The results obtained indicate that threonine levels required for optimal performance of the chickens are within the recommended dietary levels of 4 to 8 g/kg DM for broiler chickens, possibly indicating that diets containing cellulase require additional threonine to utilize additional energy generated.
Thesis (M.Sc. Agriculture (Animal Production)) -- University of Limpopo, 2023
Keywords: Threonine; Feed intake; Body weight; FCR; Meat colour; Chicken feed industry; Chicken breeds; Chickens -- Feeding and feeds; Broilers (Chickens) -- Feeding and feeds